Use of Tanδ and Partial Discharge for Evaluating the Cable Termination Assembly - Cihat Cagdas Uydur; Oktay Arikan (Energies, 2020)
It is known that the failure of cable terminations causes power outages and impairs system quality and continuity. Besides, serious economic losses on both the distribution and consumer sides occur. In this study, the dielectric behavior of the cable and the faults caused by the defects in the cable termination under overvoltage has been examined. As test samples, 12 kV XLPE insulated cable is used and they were aged at three (3*U0) and five (5*U0) times the rated voltage. After each aging cycle, dielectric parameters of the cable were measured by an OMIRCRON CPC100/CPTD1 device, and the partial discharge (PD) was measured by an OMICRON MPD600 device. In the measurements, it was observed that the cable was broken down at different aging cycle numbers as a result of defects in the cable termination due to weak workmanship. As a result of the measurements, it is concluded that defects in the cable termination give information about the increase in the probability of failure and the decrease of the cable lifetime. Consequently, it is concluded that fine workmanship and timely maintenance of cable terminations prevent the system from unwanted power outages and economic losses.